Emergency medicine simulation workbook : a tool for bringing the curriculum to life - Thoureen, Traci L.; Scott, Sara B. (Chichester, West Sussex : Wiley-Blackwell, 2013)
"This book is written and designed to provide medical educators in emergency medicine with resource for integrating medical simulation into their teaching practices. Material is provided in the form of clinical cases which are drawn from a diverse group of faculty authors from a range of major teaching centers. The cases provide readers with a full spectrum of pathology. Moreover, each case is formatted and annotated so that it can be tailored to novice or advanced learners, and easily deployed in a diversity of settings. Valuable "tips or tricks" accompany images patient data. Overall, this book is deal for use by EM educators as part of a tailored teaching and assessment portfolio"--Provided by publisher.
"This book is written and designed to provide medical educators in emergency medicine with resource for integrating medical simulation into their teaching practices"--Provided by publisher.
1. Introduction: How to use this book / Traci L. Thoureen and Sara B. Scott -- 2. Vascular emergencies / Sarah B. Dubbs and Traci L. Thoureen -- 3. Resuscitation emergencies / Albert T. Nguyen [and four others] -- 4. Gastrointestinal emergencies / Corey R. Heitz and Raymond P. Ten Eyck -- 5. Renal/electrolyte emergencies / Sara B. Scott and Catherine Pettit -- 6. Endocrine emergencies / Sarah Farris -- 7. Environmental emergencies / Moira Davenport -- 8. Obstetric emergencies / Torrey A. Laack -- 9. Pulmonary/critical care emergencies / Heather Mahoney and Ani Aydin -- 10. Toxicologic emergencies / Rodney Omron, Harry E. Herverling, and Andrew I. Stolbach -- 11. Pediatric emergencies / Jacqueline Nemer and Sandrijn van Schaik -- 12. Medical error/interpersonal communication / T. Kent Denmark [and four others] -- 13. Trauma emergencies / Traci L. Thoureen and Sara B. Scott.
Machine generated contents note: ForewordJames A. Gordon1 Introduction: How to use this bookTraci L. Thoureen and Sara B. Scott2 Vascular emergenciesSarah B. Dubbs and Traci L. Thoureen3 Resuscitation EmergenciesAlbert T. Nguyen, Dustin D. Smith, T. Kent Denmark, Andrew Bard, and James W. Rhee4 Gastrointestinal EmergenciesCorey R. Heitz and Raymond P. Ten Eyck5 Renal/Electrolyte EmergenciesSara B. Scott and Catherine Pettit6 Endocrine EmergenciesSarah Farris7 Environmental EmergenciesMoira Davenport8 Obstetric EmergenciesTorrey A. Laack9 Pulmonary Emergencies and Critical CareHeather Mahoney and Ani Aydin10 Toxicology EmergenciesRodney Omron, Harry E. Heverling and Andrew I. Stolbach11 Pediatric EmergenciesJacqueline Nemer and Sandrijn van Shaik12 Medical Error/Interpersonal CommunicationsT. Kent Denmark, Andrew Bard, Albert T. Nguyen, James W. Rhee, and Dustin D. Smith13 Trauma EmergenciesTraci L. Thoureen and Sara B. ScottIndex.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Emergency medicine -- Study and teaching; Emergency medicine -- Simulation methods; Emergency Medicine -- education; Teaching Materials; Emergencies; Manikins; Patient Simulation; Teaching -- methods; MEDICAL -- Allied Health Services -- Emergency Medical Services; MEDICAL -- Emergency Medicine; MEDICAL -- Nursing -- Emergency; Case Reports; Electronic books